2021
DOI: 10.1016/j.jamcollsurg.2020.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Plasma Metabolome after Trauma, Novel Circulating Sphingolipid Signatures, and In-Hospital Outcomes

Abstract: BACKGROUND: Trauma is the leading cause of death and disability for individuals under age 55. Many severely injured trauma patients experience complicated clinical courses despite appropriate initial therapy. We sought to identify novel circulating metabolomic signatures associated with clinical outcomes following trauma. STUDY DESIGN: Untargeted metabolomics and circulating plasma immune mediator analysis was performed on plasma collected during 3 post-injury time periods (<6 hours [h], 6 he24h, day 2eday 5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 60 publications
0
17
1
Order By: Relevance
“…The clinical data, EC, cytokines, and lipidomic data for PAMPer and all three layers for TD2 have been previously published. 21 , 22 , 23 , 24 Here, we provide an overview of the metabolomic and proteomic findings for the PAMPer cohort. Untargeted plasma metabolomics was performed on 17 non-fasting healthy controls (HCs) and 194 trauma patients at 0, 24, and 72 h after arrival to the hospital.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical data, EC, cytokines, and lipidomic data for PAMPer and all three layers for TD2 have been previously published. 21 , 22 , 23 , 24 Here, we provide an overview of the metabolomic and proteomic findings for the PAMPer cohort. Untargeted plasma metabolomics was performed on 17 non-fasting healthy controls (HCs) and 194 trauma patients at 0, 24, and 72 h after arrival to the hospital.…”
Section: Resultsmentioning
confidence: 99%
“…As these small molecules represent the end result of layered epigenomic, transcriptomic, and proteomic regulation, metabolite profiles provide an integrative view of complex biological systems. In humans, studies utilizing metabolomic methods to help delineate age-associated patterns and patient subgroups in sepsis [11], pneumonia [12], and trauma [13] have proven to be of significant value in highlighting potentially novel avenues for both basic research and potential intervention. However, human studies remain costly and time-consuming, and murine models remain a mainstay for evaluation of central metabolic pathways following insult.…”
Section: Introductionmentioning
confidence: 99%
“…Our current understanding of the metabolic response to traumatic injury is based almost entirely upon the results of studies that have analysed serum samples acquired from patients at either a single post-injury time-point [20][21][22]24,43] or at multiple timepoints during the acute injury phase (days 1-7) [23,25,26,28,44,45]. Thus, via the analysis of blood samples obtained in the acute (days 0-4), intermediate (days [5][6][7][8][9][10][11][12][13][14] and late (days 15-112) post-injury phases, our study has provided novel insights into both the kinetics of the metabolic response to injury as well as the long-term metabolomic profiles of major trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, disturbances in amino acid and fatty acid metabolism have been reported in TBI patients who experience post-traumatic cognitive impairments [21], whilst significantly increased concentrations of glucose and glutamate were measured in serum samples obtained at the time of hospital admission from non-survivors of severe trauma [20]. More recently, in a cohort of eighty-six blunt trauma patients, Cyr et al found that at days 2-5 post-injury, a plasma metabolome enriched in sphingolipids was associated with several improved clinical outcomes, which included a shorter ICU LOS [28]. However, the study did not address whether metabolomic profiles in the immediate post-injury phase could be used to predict which patients would experience an extended LOS in ICU.…”
Section: Introductionmentioning
confidence: 99%